1993
DOI: 10.1038/bjc.1993.380
|View full text |Cite
|
Sign up to set email alerts
|

Differential biological significance of tissue-type and urokinase-type plasminogen activator in human breast cancer

Abstract: Summary Plasminogen activator (PA) is a serine protease existing in two forms known as tissue-type (t-PA) and urokinase-type (u-PA). To examine whether PA is related to the postoperative clinical course of human breast cancer, total PA activity, t-PA activity, u-PA activity, and immunoreactive t-PA were determined in tissue extracts from 144 breast cancer specimens. The patients were initially divided into four groups according to the postoperative clinical course: Group I (83 patients who are disease-free), G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Consequently, the increased levels of plasmin and nattokinase itself dissolve the fibrin clot [24,25]. Major plasminogen activators are mainly divided into t-PAs and urokinase-type plasminogen activators [26,27]. Nattokinase stimulates t-PA, and plasmin is produced from plasminogen [28].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the increased levels of plasmin and nattokinase itself dissolve the fibrin clot [24,25]. Major plasminogen activators are mainly divided into t-PAs and urokinase-type plasminogen activators [26,27]. Nattokinase stimulates t-PA, and plasmin is produced from plasminogen [28].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, elastase is reported to potentiate the conversion of plasminogen to plasmin by urokinase-type plasminogen activator (Machovich & Owen, 1989), which is also synthesised by a number of tumour cells, including breast cancer cells (Cajot et al, 1986;Stump et al, 1986). Recently, a direct correlation has been found between levels of urokinase plasminogen activator activity and/or concentration and 'metastatic potential in human and rodent mammary carcinoma (Duffy et al, 1988;Janicke et al, 1990;Yamashita et al, 1992;1993b). Collagenase, which may play a role in tumour cell invasion at a neutral pH, can be activated through plasminogen activator (Paranjpe et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Both uPA and PAI-1 are established prognostic factors in several types of cancer, a high tissue level of both components generally being associated with tumour progression and with poor disease-free and/or overall survival (reviewed by Duffy, 1996;Schmitt et al, 1997). Furthermore, several investigators have reported on the potential diagnostic and prognostic relevance of tPA analysed either in plasma or in tumour tissues from patients, including those afflicted with breast or colon cancer (Layer et al, 1987;De Bruin et al, 1988;Duffy et al, 1988;Needham et al, 1988;Grøndahl-Hansen et al, 1990;Jänicke et al, 1990Jänicke et al, , 1991Rella, et al, 1993;Yamashita et al, 1993Yamashita et al, , 1995Duggan et al, 1997). In addition, some studies even have examined the presence of complexes between tPA and PAI-1 in plasma from healthy individuals and patients with various diseases (Niwano et al, 1992;Hansson et al, 1994;Maser et al, 1997).…”
mentioning
confidence: 99%